2001
DOI: 10.1054/bjoc.2000.1640
|View full text |Cite
|
Sign up to set email alerts
|

A novel doxorubicin-glucuronide prodrug DOX-GA3 for tumour-selective chemotherapy: distribution and efficacy in experimental human ovarian cancer

Abstract: Doxorubicin (DOX) is an anticancer agent with a wide spectrum of activity. Cumulative dose-related cardiotoxicity, however, is a major side-effect of DOX, in addition to the acute toxicities, such as myelosuppression, nausea and vomiting. The success of DOX, and its limitations in clinical use, have directed research endeavours for the development of analogues of DOX with an improved therapeutic index. Among these are iododoxorubicin, AD-32 and epidoxorubicin (Weiss, 1992). Iododoxorubicin was noted to be prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 22 publications
1
60
0
Order By: Relevance
“…Under the experimental conditions used, the IC 50 value for doxorubicin in OVCAR-3 cells was 5 mM, which confirmed the 2.5 mM value calculated in a previous experiment (Houba et al, 2001a). This relatively high IC 50 value could probably be explained by the use of U-bottom wells, in which the cells do not grow as a monolayer, but more like a spheroid.…”
Section: Prodrug Activation and Antiproliferative Effectssupporting
confidence: 87%
See 1 more Smart Citation
“…Under the experimental conditions used, the IC 50 value for doxorubicin in OVCAR-3 cells was 5 mM, which confirmed the 2.5 mM value calculated in a previous experiment (Houba et al, 2001a). This relatively high IC 50 value could probably be explained by the use of U-bottom wells, in which the cells do not grow as a monolayer, but more like a spheroid.…”
Section: Prodrug Activation and Antiproliferative Effectssupporting
confidence: 87%
“…Therefore, DOX-GA3 is not available for conversion by the endogenous enzyme under normal circumstances. An additional advantage of this human enzyme is the fact that, in larger tumours, the glucuronyl-doxorubicin prodrug has an inhibiting effect on tumour growth on its own (Bosslet et al, 1995;Houba et al, 2001a). The success of the glucuronyl-doxorubicin prodrug is ascribed to release of the enzyme from necrotic tumour cells and macrophages in larger tumours (Bosslet et al, 1998).…”
mentioning
confidence: 99%
“…anthracyclines and topoisomerase I inhibitors in mice bearing human xenografts 16,17,42 and suggests that even without Ad.bG transduction of cancer cells, SN-38 generated by deconjugation of SN-38G by bG in the tumor microenvironment may contribute to the antitumor activity of CPT-11. 45,46 Our study suggests several potential methods to further enhance the antitumor efficacy of CPT-11.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Glucuronide analogs of anticancer drugs can act as prodrugs that can be activated by the enzyme b-glucuronidase (bG). 16,17 This suggests that another approach to enhance CPT-11 effectiveness might be to express bG in the host to catalyze the hydrolysis of SN-38G back to SN-38. In fact, SN-38G excreted in the bile can be converted back to SN-38 by bacterially produced bG in the intestine, which is thought to contribute to the antitumor effect of CPT-11, but also produces intestinal toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we also found that Colo205 xenografts exhibited high levels of endogenous bG activity based on the imaging results using TrapG probes. Meanwhile, several studies have found that bG accumulates in the necrotic areas of human cancers (14,18,38,39). In addition, glucuronide conjugates usually exhibit enhanced solubility and decreased cell permeability (3) that greatly increases the utility and specificity of prodrugs or proprobes relying on selective hydrolysis by the bG enzyme.…”
Section: Discussionmentioning
confidence: 99%